Mitos nama perempuan dalam bahasa Jawa Kuna - Retnowati, Desti (Kejawen, 2025)
This article is aims to describe proper name of woman in old Javanese language. This analysis used qualitative research approach with applicated of semantic theory. The result of the research show that the proper name in old Javanese language many kinds model. In the Javanese society still used proper name as prestice. Proper name always joined with the other words. It is also included simbolic meaning.